Anaerobic indices of freestyle swimming performance in trained adult female swimmers - Zoeller, R. F.; Nagle, E. F.; Moyna, N. M.; Goss, F. L.; Lephart, S. M.; Robertson, R. J. (Medicine & Science in Sports & Exercise, 1998)
The relationships between the following were determined: 1.peak post-exercise blood lactate (Lapeak) and freestyle swimming performance; 2.Lapeak determined in a swimming flume and at poolside; 3.Lapeak and accumulated oxygen deficit (AOD); and 4.AOD and freestyle swimming performance. Well-trained female swimmers (N = 12) who were capable of swimming 50 yards in <30 seconds and/or 500 yards in <7 minutes served as Ss. Five tests were conducted each at least one week apart. 1.A discontinuous multi-stage submaximal flume test to enable extrapolation and prediction of supramaximal oxygen demand; 2.a multi-stage continuous test to measure maximal oxygen consumption (VO2max); 3.a single-stage supraximal swim test to measure Lapeak and AOD; 4.two swimming trials (50 and 500 yards) in the pool to measure Lapeak and performance times